2011
DOI: 10.3109/17549507.2011.573865
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of equity of rural speech-language pathology services for children: A geographic perspective

Abstract: The World Health Organization's equity objective states that there should be equal access to healthcare for equal need, regardless of location. Disparities between health services and challenges to achieving the equity objective have been documented both in Australia and around the world. However, little is known about the extent to which this objective has been met in the field of speech-language pathology in Australia. This study used structured interviews with 74 speech-language pathologists working in rura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 12 publications
1
48
0
1
Order By: Relevance
“…Those living in rural or remote regions have less access to speechlanguage pathology services than their urban-based counterparts (Graham & Cameron, 2008;Verdon et al, 2011). Economic models of healthcare based on a non-universal healthcare policy 6 restrict access to services for people with fewer economic means (Benedict, 2005) and minority groups, transient, migrant, and indigenous populations continue to have unmet need for services (Ou et al, 2011;Stow & Dodd, 2003;Winter, 2001) and experience poorer health and educational outcomes (Elwan, 1999;World Health Organization and the World Bank, 2011).…”
Section: Under-served Pwcd In Minority World Countriesmentioning
confidence: 99%
“…Those living in rural or remote regions have less access to speechlanguage pathology services than their urban-based counterparts (Graham & Cameron, 2008;Verdon et al, 2011). Economic models of healthcare based on a non-universal healthcare policy 6 restrict access to services for people with fewer economic means (Benedict, 2005) and minority groups, transient, migrant, and indigenous populations continue to have unmet need for services (Ou et al, 2011;Stow & Dodd, 2003;Winter, 2001) and experience poorer health and educational outcomes (Elwan, 1999;World Health Organization and the World Bank, 2011).…”
Section: Under-served Pwcd In Minority World Countriesmentioning
confidence: 99%
“…For services such as speech-language pathology, this is not always the case McLeod, Press & Phelan, 2010;O'Callaghan, McAllister, & Wilson, 2005;Verdon, Wilson, Smith-Tamaray, & McAllister, 2011;Wilson, Lincoln, & Onslow, 2002).…”
Section: Population-based Measures Of Developmentmentioning
confidence: 99%
“…Researchers have suggested the maximum distance that consumers are willing to travel to access services is 50 kilometres for weekly services (Verdon et al, 2011) or 65 kilometres for fortnightly services (Wilson et al, 2002). Over one third of communities in non-metropolitan NSW and Victoria are greater than 50 kilometres from a speech-language pathology service (Verdon, et al, 2011), and thus people living in those communities might be unable/unwilling to access a sufficient amount of speechlanguage pathology input. This issue is likely to have an equal, if not greater, effect in other states and territories of Australia, where communities are more widely dispersed.…”
Section: Speech-language Pathology Service Provisionmentioning
confidence: 99%
See 1 more Smart Citation
“…teacher aides), however, these models usually involve some degree of inperson contact, usually for assessment and reviews. Unfortunately, a traditional model of service delivery is out of reach for many children, and studies have found poor availability and accessibility of paediatric services in Australia, despite the range of settings and locations in which SLPs practice (17,(112)(113)(114)(115)(116)(117).…”
Section: Speech Pathology Availability and Accessibility In Australiamentioning
confidence: 99%